Advertising in teleseries. The most profitable fidelity (III) (Journal of Parents and Teachers, 2014)
During the prime time hours, TV channels compete with their best series to achieve higher audience ratings. Advertisers, in turn, compete to insert their products and advertise indirectly in these series. The formats in which advertising is introduced are diverse: blocks of spots, micropauses, sponsorships or acknowledgments. As teachers, we must teach critical guidelines which can be followed while watching series or advertisements.
Keywords: TV series; advertising; critical guidelines.